Assessing Cybersecurity Response Readiness and Return on Security Investment Strategies Among SMEs in Ecuador (Global Journal of Computer Science and Technology, 2025)
Cybersecurity remains a pressing concern for small and medium-sized enterprises SMEs particularly in developing nations where cultural structural and leadership barriers hinder proactive security adoption This study investigates the unique organizational and national culture dynamics influencing cybersecurity behaviors in Ecuadorian SMEs exploring how leadership traits risk perception and employee attitudes impact cybersecurity readiness through qualitative interviews with SME leaders across multiple sectors Using analytical frameworks such as Hofstede s cultural dimensions McClelland s motivation theory and dialectical organizational theory the research identifies five primary themes symbolic implementation of cybersecurity policies low formalization of risk response mechanisms lack of return-on-investment frameworks leadership styles that either support or hinder risk planning and widespread resistance to behavioral change Despite increasing exposure to cyber threats many SMEs remain reactive rather than strategic often lacking formal policies employee training or incident response plans Leadership personality traits play a significant role in shaping organizational prioritization of cybersecurity with achievement-oriented leaders driving more effective strategies
Keywords: cybersecurity culture; ecuadorian smes; leadership behavior; organizational change; hofstede dimensions